Design têxtil: perspectivas da estamparia industrial - OLIVEIRA, Felipe Guimarães Fleury de (2014)
This master thesis introduces aspects of textile printing in its technological context, in order to elucidate their techniques and processes. Expands this study, in the relations between the textile industry which includes the printing with the environmental parameters. Shows the importance of design and the textile designer in the challenges that can promote benefits about sustainable development solutions to the society. Reports the questions found in the case study that bring perspective to make the reflection of the designer in this industrial area.